Instant Dark Tea Alleviates Hyperlipidaemia in High-Fat Diet-Fed Rat: From Molecular Evidence to Redox Balance and Beyond - Qin, Si; He, Zhilan; Wu, Yuanjie; Zeng, Chaoxi; Zheng, Zhibing; Zhang, Haowei; Lv, Chenghao; Yuan, Yong; Wu, Haoren; Ye, Jianhui; Liu, Zhonghua; Shi, Meng (Frontiers in Nutrition, 2022)
Instant dark tea (IDT) is a new product gaining increasing attention because it is convenient and can endow significant health benefit to consumers, which is partially attributed to its high concentration of functional ingredients. However, the molecular mechanism underlying its regulatory effect on hyperlipidaemia is rarely studied. In the present study, we performed omics and molecular verification in high-fat diet (HFD)-fed rat, aiming to reveal the mechanism and provide molecular evidence. The results showed that the major bioactive components in IDT were including 237.9 mg/g total polysaccharides, 336.6 mg/g total polyphenols and 46.9 mg/g EGCG. Rats fed with IDT (0.27-0.54 g/kg for 12 weeks) significantly reduced the body weight and TC, TG, LDL-C, blood glucose and MDA, and induced the level of serum HDL-C as well as the levels of liver SOD, CAT, GSH-Px and Nrf2, compared to HFD group. For molecular mechanism study, HIDT feeding had significant impact on the gene expressions of biomarkers in lipogenesis (FABP, CD36, SCD1, Cyp4a1 and Kcnn2), lipid oxidation (PPARγ) and glucose glycosis (Gck and ENO2) in liver tissue. Moreover, further gut microbiome study found that, rats fed with IDT dramatically modified the gut microbial species at the family level, such as suppressing the increase of Proteobacteria abundance and Firmicutes/Bacteroidetes induced by HFD; HIDT significantly boosted the relative composition of beneficial bacterium Akkermansia and Rikenellaceae_RC9_gut_group and decreased the relative abundance of the harmful bacterium Ruminococcaceae_UCG-005 and Ruminiclostridium_9, compared to HFD (<0.01). Correlation analysis between microbiome and animal indicators found that, seven genera including Akkermansia, Clostridiales, Lachnospiraceae, Lachnospiraceae_UCG-010, Ruminiclostridium_9, Ruminococaceae-UCG-005 and Ruminocuccus_1, were found as potential biomarkers strongly correlated with oxidative stress and metabolism genes. For instance, Ruminococcaceae_UCG-005 was significantly correlated with body weight, TG, HDL-C, Nfr2, FABP3, SCD1, Cyp4a1 and Kcnn2. Collectively, the above data obtained in the present study had provided the primary molecular evidence for the molecular mechanism and brought in novel insights based on omics for the regulatory effect of IDT on hyperlipidemia.